2017
DOI: 10.1002/cne.24365
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the canine rostral ventricular‐subventricular zone: Morphological, immunohistochemical, ultrastructural, and neurosphere assay studies

Abstract: The mammalian ventricular-subventricular zone (V-SVZ) presents the highest neurogenic potential in the brain of the adult individual. In rodents, it is mainly composed of chains of neuroblasts. In humans, it is organized in layers where neuroblasts do not form chains. The aim of this study is to describe the cytoarchitecture of canine V-SVZ (cV-SVZ), to assess its neurogenic potential, and to compare our results with those previously described in other species. We have studied by histology, immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 95 publications
(120 reference statements)
2
14
0
Order By: Relevance
“…Proliferating cells and immature neurons were observed at all ages in the sub ventricular zone of the lateral ventricles, rostral migratory stream, olfactory bulb and sub granular zone of the hippocampal dentate gyrus. Expression of both Ki-67 and DCX confirmed that these brain regions are indeed neurogenic sites and these findings extend earlier observations made by previous researchers in mammals (Kuhn et al, 1996;Enwere et al, 2004;Kondo et al, 2010;Nada et al, 2010;Encinas et al, 2011;Jinno, 2011;Kempermann, 2011;Mobley et al, 2014;Olaleye and Ihunwo, 2014;Olude et al, 2014;Fernández-Flores et al, 2018).…”
Section: Distribution Of Ki-67 and DCX Immunoreactive Cells In The Basupporting
confidence: 90%
See 2 more Smart Citations
“…Proliferating cells and immature neurons were observed at all ages in the sub ventricular zone of the lateral ventricles, rostral migratory stream, olfactory bulb and sub granular zone of the hippocampal dentate gyrus. Expression of both Ki-67 and DCX confirmed that these brain regions are indeed neurogenic sites and these findings extend earlier observations made by previous researchers in mammals (Kuhn et al, 1996;Enwere et al, 2004;Kondo et al, 2010;Nada et al, 2010;Encinas et al, 2011;Jinno, 2011;Kempermann, 2011;Mobley et al, 2014;Olaleye and Ihunwo, 2014;Olude et al, 2014;Fernández-Flores et al, 2018).…”
Section: Distribution Of Ki-67 and DCX Immunoreactive Cells In The Basupporting
confidence: 90%
“…Our results further revealed that there was no period during the first 12 postnatal weeks where neurogenesis was stable over extended periods defining life‐history stages corresponding to juvenile, sub adult and adult. Age‐related decreases in neurogenesis in the SVZ and RMS have been reported previously in laboratory mice (Enwere et al, 2004; Luo et al, 2006; Shook et al, 2012; Mobley et al, 2014), laboratory rats (Chen et al, 2003), the giant African rat (Olude et al, 2014) and more recently dogs (Fernández‐Flores et al, 2018). These age‐related decreases in neurogenesis in the SVZ and RMS have also been proposed to be functionally linked to the olfactory dysfunction that is observed during aging (Enwere et al, 2004).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The canine brain presents many similarities with the human brain in anatomical organization, architectural complexity, gene expression (Griffiths, Duncan, Mcculloch, & Harvey, 1981;Hemsley & Hopwood, 2010;Wenger et al, 1999), physiology (Jung et al, 2010), and agerelated alterations (Cummings et al, 1996;Yu et al, 2011). Recent histological, immunohistochemical, and ultrastructural evidence suggests that the canine brain highly represents the adult human neurogenic events (Fernandez-Flores et al, 2018;Walton, Parmentier, & Wolfe, 2013). The fetal development, cytoarchitecture and neurogenic potential of the canine adult neurogenic niches were shown to share many features in common with humans (Fernandez-Flores et al, 2018;Orechio et al, 2018) establishing canines as excellent animal models for the study of adult hippocampal neurogenesis.…”
mentioning
confidence: 99%
“…Recent histological, immunohistochemical, and ultrastructural evidence suggests that the canine brain highly represents the adult human neurogenic events (Fernandez-Flores et al, 2018;Walton, Parmentier, & Wolfe, 2013). The fetal development, cytoarchitecture and neurogenic potential of the canine adult neurogenic niches were shown to share many features in common with humans (Fernandez-Flores et al, 2018;Orechio et al, 2018) establishing canines as excellent animal models for the study of adult hippocampal neurogenesis.…”
mentioning
confidence: 99%